Effects of composition and pore evolution on thermophysical properties of Huadian oil shale in retorting and oxidizing pyrolysis. (1st December 2021) - Xu, Shaotao; Sun, Youhong; Lü, Xiaoshu; Yang, Qinchuan; Li, Qiang; Wang, Zhendong; Guo, Mingyi
Graphical abstract: Highlights: Different transformations of inorganic minerals were found during the pyrolysis of oil shale. The thermophysical properties of semi-coke in oxidizing pyrolysis were investigated. The effects of composition and pore evolution on thermophysical properties of semi-coke were analyzed. Semi-coke in oxidizing pyrolysis have advantages in heat transfer properties over anaerobic retorting at low temperatures. Abstract: This chemical composition and pore evolution of oil shale during oxidizing pyrolysis (OP) and their influences on its thermophysical properties were investigated in this study. Various transformations of the minerals in oil shale were detected, among which montmorillonite was noted to transform into illite during anaerobic retorting (AR), and into kaolinite during OP. Variations in the quantities of residual carbon and organic matter during low-temperature AR and OP were noted to be possibly responsible for the difference in pore volumes. Remarkable increases in surface and volumes of mesopores and macropores through OP were observed even at low temperatures. The pore volume was proven to significantly affect the thermophysical properties of semi-cokes at low temperatures during OP. Higher thermal conductivity and thermal diffusivity were observed in semi-cokes obtained via OP at 350 ℃ compared to those obtained via AR at 520 ℃. These phenomena highlight the potential of OP for application in in-situ oil shale exploitation.